The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1590/s0102-67202013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das complicações da esofagectomia de resgate na terapêutica cirúrgica do câncer de esôfago avançado

Abstract: -Background: Even though the esophageal cancer has innumerous treatment options its prognosis is still unsettled. Because esophagectomy is rarely curative, new and emerging therapies come to light such as isolated chemotherapy and radiotherapy or combined chemoradiation, followed or not by surgery. The rescue esophagectomy is an alternative for those patients with recurrent or advanced disease. Aim: To evaluate the results of the rescue esophagectomy in patients with esophageal cancer who had previously underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…22 Um trabalho que incluiu pacientes com CE, de estô-mago e pâncreas encontrou um percentual de 2,7% de perda de peso, sendo que 64,4% dos pacientes relataram perda de peso não intencional. 23 A caquexia se caracteriza pela perda contínua de massa muscular e de gordura e está associada com a maioria dos cânceres em estágio avançado, principalmente gastrointestinal.…”
Section: Discussionunclassified
“…22 Um trabalho que incluiu pacientes com CE, de estô-mago e pâncreas encontrou um percentual de 2,7% de perda de peso, sendo que 64,4% dos pacientes relataram perda de peso não intencional. 23 A caquexia se caracteriza pela perda contínua de massa muscular e de gordura e está associada com a maioria dos cânceres em estágio avançado, principalmente gastrointestinal.…”
Section: Discussionunclassified
“…Thus, the method does not provide any quality of life, not contemplating the principles of an adequate palliative therapy. In addition, complications such as invariably aspiration bronchopneumonia, abdominal wall dehiscence, bleeding, digestive fistula with consequent mortality potential and low survival are frequently associated (5,22,23) Thus, the studies reported in the literature serve only as a historical review, since they are from the 1960s, 1970s and early 1980s, when the endoscopic methods presented today were not yet evident. Meniconi (22), in a literature review with 967 patients submitted to this type of procedure, reports complications ranging from 15 to 50%, with a mortality rate of up to 33% with survival time generally, not exceeding 90 days in most of the patients studied and without having rescued a satisfactory quality of life.…”
Section: Cirurgicalmentioning
confidence: 99%
“…However, in recent years with the most appropriate postoperative care, with teams trained and accustomed to surgical procedures in the esophagus, there was a decrease in morbidity and mortality (14,15,19,23).…”
Section: Cirurgicalmentioning
confidence: 99%
“…There are two main histological types: esophageal adenocarcinoma (EAC) and esophageal squamous cell carcinoma (ESCC), which differ in etiology, pathogenesis, and biological characteristics. Despite the rapid increase in the incidence of EAC in western countries, ESCC remains dominant in East Asia (Torre et al, 2015), with a poor 5-year overall survival (OS) rate and a high incidence of recurrence and metastasis (Aquino et al, 2013). Although the TNM staging system has been extensively employed as a factor indicating prognosis, due to the heterogeneity of ESCC, there still exist differences in the survival of patients at the same clinical stage.…”
Section: Introductionmentioning
confidence: 99%